The Effect of Education Using Poster on Mother's Self Efficacy in Kangaroo Mother Care Implementation at Panti Rahayu Hospital (STIKES Bethesda Yakkum, 2022)
Low Body Weight (LBW) infants are at risk of experiencing health problems, one of which is hypothermia. Kangaroo Mother Care (KMC) is one of the LBW care interventions to prevent hypothermia. Preliminary studies at Panti Rahayu Hospital have not shown optimum KMC due to the lack of willingness of mothers, especially primiparas with LBW babies. LBW babies’ condition made them not very confident in taking care of their babies. This research aims to know the effect of education using posters on mothers’ self-efficacy in implementing Kangaroo Mother Care at Panti Rahayu Hospital. This was pre-experimental research with pre and post-test without control. Used quota sampling with 30 respondents. The measuring instrument was a questionnaire with 20 statements. The statistical test used the Wilcoxon Test. The result showed there was a difference in self-efficacy scores between before and after treatment (p=0.000) with a significance value of 5%. There is an effect of education using posters on mothers' self-efficacy in implementing KMC at Panti Rahayu Hospital with the average difference between before and after being 15.50. Further researchers are suggested to investigate factors that affect maternal self-efficacy in implementing KMC, such as the lack of information and knowledge of mothers about KMC.